Using the Cytosensor Microphysiometer to Assess Ocular Toxicity. Issue 1 (7th August 2014) - Nash, Jennifer R.; Mun, Greg; Raabe, Hans A.; Curren, Rodger
Abstract: Measuring in vitro cytotoxicity is one method currently used to estimate damage to the eye after chemical exposure. The Cytosensor Microphysiometer method evaluates cytotoxicity by measuring the test material–induced reduction in the metabolic rate of L929 cells. Changes in metabolic rate are measured indirectly as a function of changes in the extracellular acidification rate of the cells. During exposure to increasing concentrations of a cytotoxic material, there is a decrease in the release of acid byproducts into the surrounding medium as the cells die. These acidic metabolic byproducts cause a measurable change in the pH of a lightly buffered medium, which can be measured by the Cytosensor Microphysiometer. The change in the pH of the medium over time is then converted into a metabolic rate estimate for the cells. The endpoint measurement from the assay is the metabolic rate decline of 50%, the MRD50 value (in units of mg/ml). Curr. Protoc. Toxicol . 61:1.13.1‐1.13.11. © 2014 by John Wiley & Sons, Inc.